The Role of Interactive Media in Teaching Pronunciation Through Communicative Language Teaching Approach - Aboe, Roswita Mubin; Thalib, Syamsul Bachri; Bundu, Patta (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this research is to determine the role of interactive media in teaching pronunciation with communicative approach toward students' language and cognitive mastery. This research is descriptive qualitative with data collection techniques carried out by applying pronunciation learning to certain topics from the interactive media. The sample of the research were 26 students of English education study program. Data was collected through observation, questionnaires and tests. The questionnaires were applied to obtain information related to the use of interactive media and the implementation of communicative language teaching. The final comprehension test was conducted to analyze students' cognitive mastery. The result obtained for the media-based pronunciation learning resources was 4.50 on the scale of 5.00 with a very good category, while for the chosen topic in learning pronunciation was 4.55. In terms of cognitive skills achievement, students obtained an average score of 4.35 with a good category. Meanwhile, for the media assessment and the software aspect obtained a score of 4.48, and the learning and cognitive aspect with a score of 4.50. In view of the assessment of the learning outcomes, students obtained a score of 85.12 with a good interpretation score. The role of interactive media increases students' cognitive mastery and pronunciation skills through a communicative language teaching approach